Maria Isabel Limongi interviews Yara Frateschi on the book "Liberdade, cidadania e ethos democrático: estudos antihobbesianos" (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2023)
Maria Isabel Limongi interviewed Yara Frateschi in the context of the release of the book"Liberdade, cidadania e ethos democrático: estudos antihobbesianos" in 2021. This publication arises from further reflexions on the questions posed by Maria Isabel Limongi.